(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India’s financial system became the desire of the world due to it’s unharmed nature after the global financial crisis of 2008 and the situation is not so good for the banks, as non-performing assets are increasing day by day, a stress is there on the profitability and so many banking frauds have taken place. All these elements have changed the complete scenario of banking in India. So, the present study is conducted to evaluate the financial soundness of Public Sector Banks in India. It is found in the results that all the selected Public Sector Banks are financially sound as their efficiency score exceeds the limit provided by the International Monetary Fund for the financial soundness of the banks. The most financially sound bank is the Indian Bank which is the top performer among the group for the entire study period. The solvency position of the State Bank of India has been found good as it is in the top two most solvent banks for four years out of total five years of the study.